Peran Pemerintah Desa dalam Pelestarian Nilai Budaya Perkawinan Tiga Tungku Masyarakat Adat Leworahang - Veronika Boleng Kelen; Indriyati Indriyati; Yohanes Kornelius Ethelbert; Sisilia Oliviera Mambo (PUBLICNESS: Journal of Public Administration Studies, 2025)
The Tiga Tungku (Likat Telo) customary marriage system of the Leworahang indigenous community serves as a cultural framework that maintains inter-clan balance through the roles of opu (the groom’s family) and belake (the bride’s family). However, modernization, globalization, and shifting values among younger generations have altered its meaning and weakened its social function. This study aims to analyze the role of village government in preserving the cultural values of the Tiga Tungku marriage system and to identify collaborative strategies between traditional institutions and the village government in sustaining social cohesion. Employing a qualitative ethnographic case study in Ile Padung Village, East Flores Regency, data were collected through participatory observation, in-depth interviews with traditional leaders and village officials, and document analysis. The findings reveal a shift from collective to individual orientations and a declining function of customary forums as decision-making bodies. The village government plays a strategic role by establishing the Traditional Leadership Council, formulating village regulations grounded in local wisdom, and promoting cultural education for youth. Theoretically, this study contributes to understanding the adaptation of social structures from a Lévi-Straussian perspective and offers practical insights for strengthening culture-based policy implementation at the village level.